Implementasi Internet of Things Dalam Monitoring dan Controlling Variable Frequency Drive - Pradhana, Risky Reza; Prasetyo, Bagus Alit; Syukriyah, Yenie (Jurnal Ilmiah Informatika Global, 2023)
The use of the Internet of Things (IoT) has had a significant impact in various fields, including industry and automation. IoT connects devices and systems online, enabling fast and efficient exchange of data and control. In industry, the use of IoT has changed the way systems operate and monitor, including in terms of monitoring and controlling driver 3-phase induction motors/Variable Frequency Drive (VFD). The research method used in this research is making prototypes and trials. In the first stage, a prototype monitoring and controlling system using IoT was designed and developed. This system consists of a sensor to measure motor parameters, a microcontroller as a controller, and a communication module to connect the system to the internet. The implementation of IoT in this system allows real-time collection of motor data and sending this data to a cloud server for further analysis. With the implementation of IoT in monitoring and controlling 3-phase induction motor drivers/VFD, remote motor operation becomes more possible and efficient. Motor information in the form of speed and current obtained in real-time allows the operator to take appropriate steps in optimizing motor operation.